2017
DOI: 10.1136/bmjopen-2016-012816
|View full text |Cite
|
Sign up to set email alerts
|

Association between insomnia symptoms, job strain and burnout syndrome: a cross-sectional survey of 1300 financial workers

Abstract: ObjectivesProfessional burnout is closely related to work stress but less frequently associated with disturbed sleep. This study determines whether job strain and sleep disturbances are associated risk factors of burnout among financial workers.DesignObservational study.Participants1300 employees (725 female) of a financial company.Primary measuresSelf-reported questionnaires (Maslach Burnout Inventory, Job Content Questionnaire, Sleep questionnaire based on ICSD-3 classification), the Epworth sleepiness scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 38 publications
4
49
4
3
Order By: Relevance
“…Further longitudinal studies incorporating objective sleep measures, including prospective studies using polysomnography to examine different sleep stages and sleep disorder severity, also proposed by Metlaine et al. (), are vital to determine causality within our mediation findings, and test the efficacy of sleep‐related interventions in reducing burnout.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Further longitudinal studies incorporating objective sleep measures, including prospective studies using polysomnography to examine different sleep stages and sleep disorder severity, also proposed by Metlaine et al. (), are vital to determine causality within our mediation findings, and test the efficacy of sleep‐related interventions in reducing burnout.…”
Section: Discussionmentioning
confidence: 93%
“…percent body fat). Future research in firefighters should also consider measuring and adjusting for job strain, which is known to influence burnout (Ahola & Hakanen, ; Metlaine et al., ). Finally, this study did not assess on‐duty workload (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One burnout study found a higher rate of burnout in intermediate (as opposed to high or low) management positions [37], reflecting, in our opinion, the 2-sided power struggle of a “hierarchically sandwiched” individual. Accordingly, a Swedish study [39] found the smallest incidence of burnout in business owners (as opposed to white- and blue collar workers in companies), a finding that we would explain by the hierarchically supreme position of a business owner.…”
Section: Zeitgeist Diagnosis “Burnout” May Very Likely Hide Paded Indmentioning
confidence: 99%
“…We will show below that many PADed individuals may very likely carry the Zeitgeist diagnosis “burnout” (PubMed, accessed on March 30, 2017, searching for “burnout” or “burn out” or “burn-out” and year of publication: 1990, 221 hits vs. 2016, 1,279 hits). The diagnosis “burnout” (see, e.g., [33,34,35,36,37,38,39,40,41]) has become largely socially sanctioned and culturally mainstream, removing some of the stigma attached to mental disorders, maybe even carrying, in some subcultures, an honorable connotation like the Japanese “karoshi” (from the English “crash,” signifying “overwork death”). Interestingly, karoshi (see, e.g., [42,43]) may also be a consequence of power struggles within a commercial institution and may, in some cases, be predominantly due to PAD.…”
Section: Diagnosing Padmentioning
confidence: 99%